Monitoring and characterization of canine and feline astroviruses in domestic dogs and cats in Thailand - Yu Nandi Thaw; Kamonpan Charoenkul; Chanakarn Nasamran; Ekkapat Chamsai; Waleemas Jairak; Eaint Min Phyu; Hnin Wai Phyu; Supassama Chaiyawong; Alongkorn Amonsin (Scientific Reports)
Abstract Astrovirus (AstV) is an RNA virus that causes gastroenteritis in humans and various mammal species, including dogs and cats. In this study, we conducted a survey of canine and feline astroviruses in domestic dogs and cats in Bangkok and its vicinity in Thailand. From January 2022 to December 2023, we collected a total of 1,498 rectal swab samples from domestic dogs (n = 862) and cats (n = 636) at private small animal hospitals in Bangkok, Nonthaburi, and Samut Prakran, Thailand. The positive rate for canine astrovirus (CaAstV) was 4.2% (36/862), while that of feline astrovirus (FeAstV) in cats was 10.8% (69/636). We performed complete genome sequencing of Thai-CaAstVs (n = 11) and Thai-FeAstVs (n = 12). Phylogenetic analysis revealed that Thai-CaAstVs were clustered into lineages 1, 3, and 4, while Thai-FeAstVs were grouped within FeAstV group 1. This study identifies novel CaAstV lineages in domestic dogs and represents the first molecular detection of FeAstV in cats in Thailand. Our findings provide detailed information on the genetic characteristics of CaAstVs and FeAstVs currently circulating in Thailand, highlighting challenges for potential diagnostics and future control strategies.